(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
The problem of women’s service in the police system of the developed countries of the world is very acute, one of the main goals of state policy is to improve the status of women and create equal rights and opportunities to create the necessary conditions and legal norms in order to implement the constitutional obligation. Functional all–around (crossfit) is a modern way to improve the physical training of police academies and special forces units. The need to involve women in police work is explained by the fact that this contributes to solving such tasks as effectively organizing the fight against various types of crimes committed by women and minors, and improving relations with society.